The need for knowledge among students of the fourth literary grade in the subject of history (Journal of Pharmaceutical Negative Results, 2022)
The current research aims to identify- The need for knowledge among literary fourth-grade female students.The research population consists of (928) literary fourth-grade female students for the academic year 2021-2022 in Baqubah district. In order to achieve the objectives of the research, the researcher adopted the descriptive (relational) approach as a research methodology for her study. The researcher prepared the need for knowledge scale, consisting of (30) items and she identified five alternatives for the scale (always, often, sometimes, rarely, never) and the weights of these alternatives (5, 4, 3 , 2, 1). The psychometric properties of the scale were extracted. To complete that, the tools were applied to the basic research sample of (269) female students from the research population mentioned above. Then the data has been analyzed using the statistical package for social sciences (spss) and the results were as follows:The literary fourth grade students have a need for knowledge.In light of the research results, the researcher presented a number of conclusions, and Recommendations.